ARTICULANDO OS ESPAÇOS PÚBLICO E PRIVADO: TRANSFORMAÇÕES DAS ESPACIALIDADES VIVIDAS POR MULHERES RESPONSÁVEIS PELO DOMICÍLIO, APÓS A DISSOLUÇÃO CONJUGAL NA CIDADE DE PONTA GROSSA – PARANÁ. - Przybysz, Juliana (2011)
This dissertation aims to comprehend the space transformations lived by women who are the home responsible after marriage dissolution in Ponta Grossa city, located in Paraná State. The process of marriage dissolution besides the kids guard by the mother has been creating families which are leaded by women. Although, this phenomenon is usual in every income zone, the families which live in poor outskirts are in a vulnerable group to poverty and fragility to the citizens rights. To achieve the goal of the research, it was made a survey with the process at Segunda Vara de Família in Ponta Grossa, in categories of Separation, Divorce and Food, in the period of 2003 to 2007, involving families between zero to two minimum wage with children under twelve years old. There were selected five hundred twenty two process, related to the social limits established as well as effected analysis about the key categories. The interviews were written and analyzed by discursive analysis technique and frequency of evocation, building the meaning logic about the special experiences lived by the women in focus in the research. The space lived by the women who lead the families modify itself after marriage separation, it has been articulating in a different way of the public and private level in the urban area. The womanliness is lived to articulate de scales of home and the city, showing that the women experience many scales in simultaneous and complex ways.